24=6(-e-)

Simple and best practice solution for 24=6(-e-) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=6(-e-) equation:



24=6(-e-)
We move all terms to the left:
24-(6(-e-))=0
We add all the numbers together, and all the variables
-(6(-1e))+24=0
We calculate terms in parentheses: -(6(-1e)), so:
6(-1e)
We multiply parentheses
-6e
Back to the equation:
-(-6e)
We get rid of parentheses
6e+24=0
We move all terms containing e to the left, all other terms to the right
6e=-24
e=-24/6
e=-4

See similar equations:

| −5(3x−23)=2(x−6)−9 | | 4y2/5=-5 | | 100=4v-20v=30 | | p+3−5=5p−8−14p | | 2-x-4=3x+(-5) | | 11=1/2(7x) | | 3w+2.89=10 | | 5x+7=-71-3x | | -4/5x-12=24 | | 1/4k+1/2(1/2k+4)=25 | | X-8y=38 | | x^2-5x-36=-5x | | (4c+5)+(7c-13)=360 | | 9m=2/0 | | 2(5x-15=18 | | n/8-9=5 | | 5x3=28 | | 2-x+4+4x=x+5 | | -0.3-4.3x=-15.78 | | 918678w=109891819+198288w | | 2(x+1)=(x-2)/3 | | 4c-8=6c-18 | | 3.5x-13.5+15x=8.7 | | -11=-6-3(2c=4)-c | | 6x/7-4x/7= | | 5/x=30/7 | | 2+9n=18 | | 2(x+1)=x-2/3 | | 44=6(1=4c)-5c | | A=3k-8 | | 1+ss=1 | | 14e=430 |

Equations solver categories